2009
DOI: 10.3748/wjg.15.3516
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and disorders of mineral metabolism in chronic liver disease

Abstract: AIM:To estimate the prevalence and identify the risk factors for metabolic bone disease in patients with cirrhosis. METHODS:The study was performed on 72 Indian patients with cirrhosis (63 male, 9 female; aged < 50 years). Etiology of cirrhosis was alcoholism (n = 37), hepatitis B (n = 25) and hepatitis C (n = 10). Twenty-three patients belonged to Child class A, while 39 were in class B and 10 in class C. Secondary causes for metabolic bone disease and osteoporosis were ruled out. Sunlight exposure, physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
70
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 24 publications
16
70
5
Order By: Relevance
“…Previous studies have shown inconsistent results about the correlation between serum vitamin D level and the severity of liver dysfunction. Our results are in line [3,19] with some studies, and in contradiction to some other studies [16,20]. Our study also showed a significant correlation between low serum vitamin D level and markers of liver function insufficiency including coagulopathy, hypoalbuminemia, hyperbilirubinemia, and thrombocytopenia, in agreement with other studies [21][22][23].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Previous studies have shown inconsistent results about the correlation between serum vitamin D level and the severity of liver dysfunction. Our results are in line [3,19] with some studies, and in contradiction to some other studies [16,20]. Our study also showed a significant correlation between low serum vitamin D level and markers of liver function insufficiency including coagulopathy, hypoalbuminemia, hyperbilirubinemia, and thrombocytopenia, in agreement with other studies [21][22][23].…”
Section: Discussionsupporting
confidence: 76%
“…Although in advanced stages of CLD, from any cause, bone mass loss is frequently (20-60%) evident [3,4], the clinical relevance of vitamin D-parathyroid hormone (PTH) disturbances in hepatic osteodystrophy is still unclear. The intestinal absorption of cholecalciferol (vitamin D3) and 25-hydroxycholecalciferol is affected only in the presence of severe cholestasis.…”
Section: Introductionmentioning
confidence: 99%
“…Our results comply with those of previous reports [30][31][32][33][34][35], but the loss of bone mass among our subjects was significantly lower than has been found by some other authors. We believe that this is due to the decreased severity of hepatic impairment presented by our patients.…”
Section: Discussionsupporting
confidence: 92%
“…A similar opinion was presented by Javad et al (12) who reported that, in patients with viral B or C cirrhosis, osteopenia and osteoporosis were recorded in 42% and 26% of patients, respectively. High frequency of reduced bone density was reported by George et al (13) who described 72 patients with alcoholic and viral cirrhosis out of whom 68% had lower bone mineral density.…”
Section: Discussionmentioning
confidence: 80%
“…George et al (13) while analyzing a group of 72 patients with viral liver cirrhosis confirmed lower osteocalcin values in 68% of subjects and increased free deoxypyridinoline in 79% of patients. Sub sequently, Goral et al (10) reported that lower values of osteocalcin as a marker of bone formation were found in patients with virus B and C liver cirrhosis.…”
Section: Discussionmentioning
confidence: 93%